MORPHOMETRIC CHANGES OF FETUSES AND NEWBORNS’ HEPATOCYTES, BORNS FROM MOTHERS WITH DIABETES MELLITUS - Проценко, О.С.; Сорокіна, І.В.; Шерстюк, С.О.; Ремнева, Н.О. (World of Medicine and Biology, 2014)
The morpho-functional changes of liver of fetus and newborn, born to mothers with diabetes mellitus have been studied studied. It has been established that the degree of expression of morphological changes of liver of newborn depends on severity of mother’s DM. With the growth of DM severity, necrobiosis , fatty dystrophy and sclerotic changes develop in the liver. Maximal tension adaptation reactions is registered in the liver of newborn, born to mothers with moderate DM, while in severe DM they are exhausted.